Displaced thinned single-mode fiber Mach-Zehnder interferometer tested for temperature and curvature applications - Leonardo J. Arevalo-Bautista; Romeo Selvas-Aguilar; Juan M. Sierra-Hernandez; Eloisa Gallegos-Arellano; Mario A. Rico-Mendez; Pedro J. Fernandez de Cordoba-Castella; Daniel Toral-Acosta (Results in Optics)
This article explains the features and qualities of employing a thinned manufacturing fiber to assemble a Mach-Zehnder interferometer (MZI) for detecting two physical variables: temperature and curvature. The MZI comprises a filter by splicing core-offset sections of a thinned fiber (TF) cladding diameter of 80 μm in an SMF-TF-SMF configuration. The TF splices act as the arms of the MZI, while the mismatch diameter sections serve as optical fiber couplers. The optical spectrum analyzer (OSA) detects the transmitted light and analyzes its optical transmission characteristics, showing 11 peaks of modal interferences into the longitude region. As a result of the experimental arrangement, the curvature and temperature sensitivities are 0.49 nm/m−1, 0.01 nm/°C, and 0.09 nm/°C for temperatures of 0–60 °C and 70–130 °C, respectively. The proposed sensor has potential advantages for measuring refractive index, pH, torsion, curvature, and temperature.